KEPUASAN MASYARAKAT TERHADAP PELAYANAN PENERBITAN E-KTP DI KECAMATAN BUNGARAYA KABUPATEN SIAK - Agusrianto "; Ashaluddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This Study aims to determine Community Satisfaction With The Servis Of Issuing E-KTP In Bungaraya Districts In Siak Regency. The method used is to use a survey method with technical quantitative analysis. As for the formulation of the problem in this study (1) What is the satisfaction of the Bungaraya Community with the E-KTP issuance in Siak Regency?.(2) How is the E-KTP issuance service received by the Bungaraya community?. Data collection techniques in this study were in the form of questionnaires, obsevation, documentation. This research was conducted in Bungaraya district in Siak Regency. The data analysis technique in this study is descriptive quantitative. The results of the explained that the results of the questionaire answered that there was community satisfaction with the service for issuing E-KTP in Siak Regency, where the community is satisfied with the service provided by the E-KTP issuance service officer at the civil registry office in Siak Regency. Keywords : Community Satisfaction, Elektronik-KTP, Issuance Service.